1986
DOI: 10.2737/int-gtr-208
|View full text |Cite
|
Sign up to set email alerts
|

Supplement to The User's Guide for The Stand Prognosis Model-version 5.0

Abstract: Version 4.0 of the Prognosis Model was released in September 1981. Since then, a regeneration establishment model has been completed and small-tree increment models have been greatly refined. The COVER model has also been added to predict shrub development and total canopy cover. Thus, the representation of the vegetative component of the stand is basically complete and the Stand Prognosis Model can be linked more readily to models for nontimber resources.New management options have been added to the system, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 4 publications
1
44
0
1
Order By: Relevance
“…The choice of a diameter and top height growth function provides a final steady growth state. The diameter increment function as defined by Wykoff (1986), Hilt (1983), and Shifley (1987) are not suitable for these plantations since plants of these reforested sites are in the early stages of development and diameter growth and diameter increment are linear functions of current basal diameter or basal area. Even though the model estimates tree basal diameter, top height, and volume of trees in different site indexes, it uses stand attributes as explanatory variables as average volume of all trees, site index, and stand density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of a diameter and top height growth function provides a final steady growth state. The diameter increment function as defined by Wykoff (1986), Hilt (1983), and Shifley (1987) are not suitable for these plantations since plants of these reforested sites are in the early stages of development and diameter growth and diameter increment are linear functions of current basal diameter or basal area. Even though the model estimates tree basal diameter, top height, and volume of trees in different site indexes, it uses stand attributes as explanatory variables as average volume of all trees, site index, and stand density.…”
Section: Resultsmentioning
confidence: 99%
“…They include whole stand, stand class, and single tree models (Clutter et al, 1983;Vanclay, 1995;Peng, 2000 northern Mexico (Aguirre-Bravo, 1987;Návar et al, 1996;Zepeda-Bautista and Dominguez-Pereda, 1998). Stand class models simulate growth and yield of tree classes within the stand and individual tree models contain a list of each tree in the stand (Botkin et al, 1972;Moser, 1976;Shugart, 1984;Wykoff, 1986;Vanclay, 1994Vanclay, , 1995Peng, 2000). None of these three types of growth models have been tested in reforested sites of the Sierra Madre Occidental mountain range of northern Mexico.…”
Section: Aboveground Stand Carbon Estimatesmentioning
confidence: 99%
“…The maximum crown area equations developed by Wykoff et al (1982) were used in this study. For complex stands, Wykoff et al (1982), Wykoff (1986), and Ritchie and Hann (1987) suggested that basal area per ha for trees larger than the subject tree (BAL) (m 2 /ha) would help indicate competition. Using these two variables resulted in: [4] where ␤ 4 and ␤ 5 are parameters to be estimated.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Most of these models include competition measures (e.g., density, crown competition factor), tree size (e.g., breast height diameter, tree height, age), and site (e.g., elevation, slope, aspect) variables (Wykoff 1986, Hynynen 1995, Hasenauer and Monserud 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization studies may provide a discriminating test of a model, as Monserud (1989) reported that his optimizer was remarkably efficient at exploiting seemingly minor quirks in the Prognosis model (Stage 1973, Wykoff et al 1982, Wykoff 1986) to arrive at unrealistic solutions. Thus optimization studies coupled with expert insights may provide a good basis for model criticism.…”
Section: Logical and Biological Consistencymentioning
confidence: 99%